2012
DOI: 10.1007/s13197-012-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrolases in the loss of firmness and of the changes in sugar content during the post-harvest maturation of Carica papaya L. var solo 8

Abstract: Fruit ripening is associated with many hydrolase activities involved in the softening of the fruit during the maturation. This study investigates the relationship between the loss of firmness along with the changes of sugar content and the enzymatic activities in Carica papaya L.var solo 8 during post-harvest storage. Three maturation stages (green immature: the fruit is entirely green, green mature: the fruit shows 1/32 yellow skin and fully mature: the fruit shows 1/8 yellow skin) have been selected and stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
1
19
0
4
Order By: Relevance
“…This, in turn, due to the decomposition of the cell walls, increases the sugar levels in the cell. Besides, according to Yao et al (2012), it can explain the magnitude and direction of the correlation observed between PF and SS (-0.65). A similar result for this correlation (-0.81) was described by Oliveira et al (2012), but the authors did not explain the origin of such correlation.…”
Section: Resultsmentioning
confidence: 97%
“…This, in turn, due to the decomposition of the cell walls, increases the sugar levels in the cell. Besides, according to Yao et al (2012), it can explain the magnitude and direction of the correlation observed between PF and SS (-0.65). A similar result for this correlation (-0.81) was described by Oliveira et al (2012), but the authors did not explain the origin of such correlation.…”
Section: Resultsmentioning
confidence: 97%
“…Por ser um fruto que apresenta quantidadestraço de amido na polpa, a variação no teor de SS após a colheita é muito pequena e, quando ocorre, é resultado da degradação da parede celular, que aumenta a liberação de pectina solúvel nos espaços intercelulares, contribuindo com um ligeiro aumento no teor de SS (YAO et al, 2014). Apesar de a infiltração de CaCl 2 nos frutos ter resultado em manutenção da FF e FM por mais tempo que o observado para os frutos do controle (Figuras 3A e 3B), a partir do 9º DAT, essas apresentavam valores iguais ao dos frutos do controle, sem contudo provocar aumento no teor de SS.…”
Section: Firmezaunclassified
“…O fato de o mamão não apresentar variações no teor de SS durante sua pós-colheita (YAO et al, 2014), indica que esse atributo pode não ser adequado para diferenciar o efeito da infiltração de soluções de CaCl 2 na pós-colheita do mamão, como o indicado por Valero e Serrano (2010).…”
Section: Firmezaunclassified
“…The limitations of papaya marketing and distribution are associated with the softening phenomenon derived from the natural ripening process. One of the main challenges in papaya trading is related to its shelf‐life duration (Fabi, Cordenunsi, Seymour, Lajolo, & do Nascimento, 2009), so that the proper ripe stage selection for commercialization is relevant in the transport and storage of the fruit aiming to preserve its quality (Miller & McDonald, 1999; Yao et al., 2014).…”
Section: Introductionmentioning
confidence: 99%